TEACHER PERFORMANCE IS REVIEWED BASED ON THE PRINCIPAL'S LEADERSHIP AND SCHOOL CULTURE AT PEMATANG SIANTAR FAMILY FOUNDATION PRIVATE HIGH SCHOOL - Efendi Efendi; Sherly Sherly; Andy Wijaya; Erbin Chandra; Sisca Sisca (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The research objective is to determine the impact of principal leadership and school culture on teacher performance. The approach used in the research design is a qualitative descriptive approach and a quantitative descriptive approach. This study uses a test of validity, reliability, normality, simple linear regression, correlation and determination, the Ftest and t test with the results of the study, namely a positive and significant effect between principal leadership and school culture on teacher performance and a moderately high level of relationship. The contribution of principal leadership and school culture on teacher performance was 73,1%